Glass fiber direct yarn sizing agent, its preparation method and application
Patent Information
- Application Number
- CN202611315807.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的主要目的在于提供一种玻璃纤维直接纱用浸润剂及其制备方法和应用,以解决现有技术中玻璃纤维编织制品在高速编织过程中难以兼顾优良的顺畅性、少毛羽、良好的树脂浸透性与强力学性能的技术问题
[0016]应用本发明的技术方案,本申请的以上制备方法具有以下优势:硅烷偶联剂是玻璃纤维浸润剂体系中的关键组分,其核心功能在于构建无机玻璃表面与有机高分子材料之间的稳定界面桥梁。该作用的实现依托其独特的双亲分子结构,成膜剂构成玻璃纤维浸润剂配方中的主要固体组分,其性能对纤维的关键工艺与最终使用性能具有决定性影响。具体而言,一方面,成膜剂不仅有助于增强单丝间的抱合作用并提升保护膜的耐磨性,从而有利于优良的纤维成型效果与集束性;另一方面,有助于改善纱线在高速加工条件下的通过性,减少毛羽、散丝等缺陷的产生。同时,成膜剂的特性对纤维与树脂基体的界面结合质量有重要影响,是获得优异界面粘结强度及复合材料宏观力学性能的关键因素之一。将硅烷偶联剂与成膜剂配合使用,在确保纤维集束性和耐磨性的同时,有效避免了过量硅烷偶联剂导致的界面脆化问题,以及因成膜剂不足引发的毛羽增多现象,该硅烷偶联剂与成膜剂的复配体系能够降低纤维表面能,利于树脂快速渗透,从而满足高线速度拉挤工艺的生产需求。此外,将浸润剂的固含量控制在上述范围,有助于促进浸润剂在高速拉丝过程中的良好流动性与涂覆均匀性,降低了高固含量导致的粘度大、成膜厚及低固含量导致的烘干能耗高、分布不均的风险;又进一步促进了硅烷偶联剂充分水解及界面交联网络的稳定形成。由此,通过控制各组分的含量在以上范围内,能够更充分的实现其相互协同作用,从而使采用本申请浸润剂涂覆的玻璃纤维,兼具广谱树脂相容性、超高速浸润能力、极低毛羽、优异的工艺顺畅性及界面性能;可广泛适用于环氧、聚酯等多种树脂体系,并适用于缠绕、拉挤、编织等多种成型工艺,尤其适用于要求严苛的单股拉挤复合材料领域,所制备的复合材料力学性能优异。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass fiber sizing agents, and more specifically, to a sizing agent for direct glass fiber yarn, its preparation method, and its application. Background Technology
[0002] Glass fiber, as a key reinforcing material for high-performance composite materials, is widely used in important fields such as infrastructure, transportation, new energy, and power equipment. Among them, pultrusion molding process continues to expand its market size due to its high efficiency and continuous manufacturing advantages. Single-strand pultrusion, as a core form of this process, directly uses a single bundle of parallel untwisted direct yarn as the axial reinforcement, and its performance directly determines the quality of the final product and the production efficiency.
[0003] As downstream demands for production efficiency and product performance continue to rise, modern pultrusion technology is evolving towards higher speeds and wider compatibility with resin systems. However, existing general-purpose direct yarn wetting agents face multiple challenges in addressing this trend: First, they only offer basic compatibility with diverse resins, making it difficult to achieve excellent interfacial bonding across different resins; second, at high linear speeds, it is difficult to ensure instantaneous and sufficient wetting of fiber bundles, easily leading to incomplete wetting defects; third, extremely high process smoothness is required, as excessive yarn hairiness exacerbates die wear, and yarn fraying and lifting also affect the continuity of production, causing losses in production efficiency and economy.
[0004] Therefore, developing a special sizing agent for glass fiber direct yarn with broad-spectrum resin compatibility, ultra-high-speed wetting capability, extremely low hairiness, and excellent process smoothness has become a key to promoting industrial upgrading. Summary of the Invention
[0005] The main objective of this invention is to provide a sizing agent for direct glass fiber yarn, its preparation method, and its application, in order to solve the technical problem in the prior art that it is difficult to simultaneously achieve excellent smoothness, low hairiness, good resin penetration, and strong mechanical properties in high-speed weaving of glass fiber woven products.
[0006] To achieve the above objectives, according to one aspect of the present invention, a sizing agent for direct glass fiber yarn is provided. The sizing agent comprises an effective component and water, and the solid content of the sizing agent is 5 wt% to 9 wt%. Based on the percentage of the solid mass of each effective component to the total solid mass of the sizing agent, the effective component comprises: 5 to 30% of a silane coupling agent, 32 to 75% of a film-forming agent, 5 to 25% of a lubricant, 1 to 9% of a crosslinking agent, 1 to 8% of a compatibilizer, and 1 to 7% of a pH adjuster. The film-forming agent comprises a first film-forming agent and a second film-forming agent. The first film-forming agent is selected from any one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and phenolic type epoxy resin, and the second film-forming agent is selected from any one or more of isophthalic unsaturated polyester, orthophthalic unsaturated polyester, and dicyclopentadiene unsaturated polyester.
[0007] Further, the mass ratio of the first film-forming agent to the second film-forming agent is 2:1 to 6:1; and / or, the first film-forming agent is a hydrogenated bisphenol A type epoxy resin emulsion; the second film-forming agent is an aqueous isophthalic type unsaturated polyester emulsion; and / or, the molecular weight of the first film-forming agent is 800 to 1500; the molecular weight of the second film-forming agent is 600 to 1200.
[0008] Furthermore, the silane coupling agent is a mixture of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent, and the mass ratio of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent is 8~20%:3~12%:2~5%.
[0009] Furthermore, the aminosilane coupling agent is a diamino silane; the vinylsilane coupling agent is a vinyl silane containing an alkenyl ether group; and the epoxysilane coupling agent is an epoxy-terminated hyperbranched polysiloxane.
[0010] Further, based on the percentage of the solid mass of each effective component to the solid mass of the wetting agent, the effective components include: 7-26% silane coupling agent, 35-70% film-forming agent, 7-22% lubricant, 2-7% crosslinking agent, 1.5-6.5% compatibilizer, and 1.5-6% pH adjuster; preferably, the effective components include: 10-22% silane coupling agent, 46-63% film-forming agent, 9-18% lubricant, 3-6% crosslinking agent, 2-4.5% compatibilizer, and 2-4% pH adjuster.
[0011] Furthermore, the lubricant is a mixture of fatty acid esters and modified silicone oils, preferably a mixture of oligomeric fatty acid ester derivatives and reactive polyether modified silicone oils; and / or, the pH adjuster is citric acid and / or glacial acetic acid.
[0012] Furthermore, the crosslinking agent is a carbodiimide crosslinking agent; and / or, the compatibilizer is a phenylboronic acid graft copolymer.
[0013] According to another aspect of the present invention, a method for preparing the above-mentioned sizing agent for direct glass fiber yarn is provided, comprising: step S1: mixing raw materials including water, pH adjuster and silane coupling agent to obtain a first mixed solution; step S2: mixing a film-forming agent and a lubricant with the first mixed solution to obtain a second mixed solution; step S3: adding water to the second mixed solution to obtain a third mixed solution, wherein the mass percentage of water in the third mixed solution is ≥75%; step S4: mixing a crosslinking agent and a compatibilizer with the third mixed solution to obtain a fourth mixed solution; and step S5: adding the remaining water to the fourth mixed solution to obtain the sizing agent.
[0014] According to another aspect of the present invention, a glass fiber is provided, which is produced by coating with an impregnating agent, wherein the impregnating agent is the above-mentioned impregnating agent for direct yarn of glass fiber, or the impregnating agent is prepared by the above-mentioned preparation method.
[0015] According to another aspect of the present invention, the application of the glass fiber direct yarn impregnating agent as described above in the preparation of glass fiber composite yarn is provided.
[0016] The preparation method described in this application, using the technical solution of the present invention, has the following advantages: Silane coupling agent is a key component in the glass fiber sizing agent system, and its core function is to construct a stable interfacial bridge between the inorganic glass surface and the organic polymer material. This function relies on its unique amphiphilic molecular structure. The film-forming agent constitutes the main solid component in the glass fiber sizing agent formulation, and its performance has a decisive influence on the key processes and final performance of the fiber. Specifically, on the one hand, the film-forming agent not only helps to enhance the cohesion between monofilaments and improve the wear resistance of the protective film, thus contributing to excellent fiber forming effect and bundle properties; on the other hand, it helps to improve the yarn's permeability under high-speed processing conditions and reduce defects such as fuzz and loose fibers. Simultaneously, the characteristics of the film-forming agent have a significant impact on the interfacial bonding quality between the fiber and the resin matrix, and are one of the key factors in obtaining excellent interfacial bonding strength and macroscopic mechanical properties of the composite material. By using silane coupling agents in combination with film-forming agents, fiber bundle cohesion and abrasion resistance are ensured while effectively avoiding interfacial embrittlement caused by excessive silane coupling agents and increased fuzzing due to insufficient film-forming agents. This compound system of silane coupling agents and film-forming agents can reduce fiber surface energy, facilitating rapid resin penetration and thus meeting the production requirements of high-linear-speed pultrusion processes. Furthermore, controlling the solid content of the sizing agent within the aforementioned range helps promote good flowability and coating uniformity during high-speed fiber drawing, reducing the risks of high viscosity and thick film due to high solid content, and high drying energy consumption and uneven distribution due to low solid content. It also further promotes the complete hydrolysis of the silane coupling agent and the stable formation of the interfacial cross-linking network. Therefore, by controlling the content of each component within the above range, their synergistic effect can be more fully realized, so that the glass fiber coated with the sizing agent of this application has broad-spectrum resin compatibility, ultra-high speed wetting ability, extremely low fuzz, excellent process smoothness and interfacial properties; it can be widely used in various resin systems such as epoxy and polyester, and is suitable for various molding processes such as winding, pultrusion and weaving, especially suitable for the field of single-strand pultrusion composite materials with strict requirements, and the prepared composite material has excellent mechanical properties. Detailed Implementation
[0017] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0018] As analyzed in the background section of this application, existing technologies have difficulties in achieving excellent smoothness, low fuzziness, good resin impregnation, and strong mechanical properties in high-speed weaving of glass fiber woven products. In order to solve the above problems, this application provides a glass fiber direct yarn impregnating agent, its preparation method, and its application.
[0019] In a typical embodiment of this application, a sizing agent for direct glass fiber yarn is provided. The sizing agent comprises an effective component and water, and the solid content of the sizing agent is 5wt% to 9wt%. Based on the percentage of the solid mass of each effective component to the total solid mass of the sizing agent, the effective component comprises: 5-30% silane coupling agent, 32-75% film-forming agent, 5-25% lubricant, 1-9% crosslinking agent, 1-8% compatibilizer, and 1-7% pH adjuster. The film-forming agent comprises a first film-forming agent and a second film-forming agent. The first film-forming agent is selected from any one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and phenolic type epoxy resin, and the second film-forming agent is selected from any one or more of isophthalic unsaturated polyester, orthophthalic unsaturated polyester, and dicyclopentadiene unsaturated polyester.
[0020] Silane coupling agents are key components in glass fiber impregnation systems, their core function being to construct a stable interfacial bridge between the inorganic glass surface and the organic polymer material. This function relies on their unique amphiphilic molecular structure. Film-forming agents constitute the main solid component in glass fiber impregnation formulations, and their performance has a decisive impact on the key processes and final performance of the fibers. Specifically, on the one hand, film-forming agents not only help enhance the cohesion between monofilaments and improve the abrasion resistance of the protective film, thus contributing to excellent fiber forming and bundling; on the other hand, they help improve the yarn's permeability under high-speed processing conditions, reducing defects such as fuzz and loose fibers. Simultaneously, the characteristics of film-forming agents have a significant impact on the interfacial bonding quality between the fiber and the resin matrix, and are one of the key factors in obtaining excellent interfacial bond strength and macroscopic mechanical properties of composite materials. By using silane coupling agents in combination with film-forming agents, fiber bundle cohesion and abrasion resistance are ensured while effectively avoiding interfacial embrittlement caused by excessive silane coupling agents and increased fuzzing due to insufficient film-forming agents. This compound system of silane coupling agents and film-forming agents can reduce fiber surface energy, facilitating rapid resin penetration and thus meeting the production requirements of high-linear-speed pultrusion processes. Furthermore, controlling the solid content of the sizing agent within the aforementioned range helps promote good flowability and coating uniformity during high-speed fiber drawing, reducing the risks of high viscosity and thick film due to high solid content, and high drying energy consumption and uneven distribution due to low solid content. It also further promotes the complete hydrolysis of the silane coupling agent and the stable formation of the interfacial cross-linking network. Therefore, by controlling the content of each component within the above range, their synergistic effect can be more fully realized, so that the glass fiber coated with the sizing agent of this application has broad-spectrum resin compatibility, ultra-high speed wetting ability, extremely low fuzz, excellent process smoothness and interfacial properties; it can be widely used in various resin systems such as epoxy and polyester, and is suitable for various molding processes such as winding, pultrusion and weaving, especially suitable for the field of single-strand pultrusion composite materials with strict requirements, and the prepared composite material has excellent mechanical properties.
[0021] In one embodiment of this application, the mass ratio of the first film-forming agent to the second film-forming agent is 2:1 to 6:1; and / or, the first film-forming agent is a hydrogenated bisphenol A type epoxy resin emulsion; the second film-forming agent is an aqueous isophthalic unsaturated polyester emulsion; and / or, the molecular weight of the first film-forming agent is 800 to 1500; and the molecular weight of the second film-forming agent is 600 to 1200.
[0022] Furthermore, by compounding the two film-forming agents in the above proportions, the advantages of a rigid skeleton and a flexible reactive layer can be complemented. When the mass ratio of the first film-forming agent to the second film-forming agent is within the above range, the composite film layer of the sizing agent has sufficient rigidity to ensure the smooth implementation of fiber bundling and processes, and can also promote its rapid fusion and firm bonding with various resins through flexible segments and reactive functional groups, thereby helping the fiber to obtain excellent interfacial properties in various resins.
[0023] The film-forming agent used in this application is preferably a composite system of epoxy resin emulsion and unsaturated polyester emulsion. Specifically, in the first film-forming agent, a hydrogenated bisphenol A structure with a molecular weight above the specified range is preferred. This structure retains the high reactivity of the epoxy groups while improving the flexibility and hydrolysis resistance of the molecular chain. Within the specified molecular weight range, it facilitates the formation of a strong and durable continuous protective film, thereby not only promoting improved yarn bundle properties and significantly reducing fuzz generation during processing, thus facilitating smooth pultrusion processes, but also its viscosity and excellent film-forming flowability promote rapid wetting and spreading of subsequent resins, facilitating ultra-high-speed wetting. In the second film-forming agent of this application, an isophthalic structure with a molecular weight above the specified range is preferred, endowing it with higher heat resistance and mechanical strength. The abundant ester bonds and unsaturated double bonds in the molecular chain give it good compatibility with unsaturated polyesters, vinyl esters, and other resins, allowing it to directly participate in the resin curing reaction. This constructs a direct chemical bonding channel at the fiber-resin interface, enhancing interfacial bonding and becoming a key factor in achieving high-performance interfaces under broad-spectrum resin compatibility conditions.
[0024] In one embodiment of this application, the silane coupling agent is a mixture of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent, and the mass ratio of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent is 8~20%:3~12%:2~5%.
[0025] This application uses a mixture of aminosilane coupling agents, vinylsilane coupling agents, and epoxysilane coupling agents as the silane coupling agent components. In this ternary coupling agent system, each component undertakes a clear and complementary interfacial function. The aminosilane coupling agent, as the main component, helps the silane coupling agent system possess sufficient anchoring points and basic reactivity. The vinylsilane coupling agent, as an important functional supplement and property extension, can fully demonstrate its interfacial reinforcement effect on free radical-cured resins. The epoxysilane coupling agent, as a key synergistic component, constructs an effective three-dimensional reinforcing network on the glass fiber surface, which is beneficial for improving the toughness and processing performance of the composite material. Simultaneously, it reduces the risk of adverse effects on the uniformity and storage stability of the wetting agent due to excessive viscosity or too many reaction sites, resulting in more outstanding reaction efficiency and stability on the glass fiber surface.
[0026] This application sets the mass ratio of aminosilane coupling agent, vinylsilane coupling agent, and epoxysilane coupling agent within the aforementioned range. The aminosilane coupling agent serves as the main component, and this range helps the silane coupling agent system possess sufficient anchoring points and basic reactivity. The vinylsilane coupling agent, as an important functional supplement and property extension, is also set within the aforementioned range. This ensures that its interfacial reinforcement effect on cationic and free radical cured resins is fully realized, while reducing the risk of compatibility imbalance in general resins due to excessive addition. The epoxysilane coupling agent, as a key synergistic component, is controlled within the aforementioned range to sufficiently construct an effective three-dimensional reinforcing network on the glass fiber surface. This is beneficial for improving the toughness and processing performance of the composite material, while reducing the risk of adverse effects on the uniformity and storage stability of the wetting agent due to excessive viscosity or too many reaction sites.
[0027] In one embodiment of this application, the aminosilane coupling agent is a diamino silane; the vinylsilane coupling agent is a vinyl silane containing an alkenyl ether group; and the epoxysilane coupling agent is an epoxy-terminated hyperbranched polysiloxane.
[0028] In this application, more preferably, the aminosilane coupling agent is a diamino silane, the vinylsilane coupling agent is a vinylsilane containing an alkenyl ether group, and the epoxysilane coupling agent is an epoxy-terminated hyperbranched polysiloxane. That is, the above-mentioned ternary coupling agent system includes a diamino silane, an alkenyl ether-containing vinylsilane, and an epoxy-terminated hyperbranched polysiloxane, with each component undertaking a clear and complementary interfacial function. Specifically, the diamino silane coupling agent, as the basic and core component of the system, has amino functional groups that, on the one hand, form a stable chemical anchor with the glass fiber surface through high activity; on the other hand, due to its excellent catalytic activity and broad reaction range, it can bond with the functional groups of various resins and provide catalytic action for the curing reaction. This is key to ensuring high-strength chemical bonding and interfacial reactivity with various resins. Vinyl silane coupling agents containing alkenyl ether groups are key components for functional expansion. Their alkenyl ether structure not only retains the ability to undergo free radical copolymerization with traditional unsaturated polyesters and vinyl ester resins, but also introduces reactivity towards cationic curing systems, which helps to expand the range of resin systems to which the sizing agent is compatible. Furthermore, epoxy-terminated hyperbranched polysiloxanes play a dual role as "interface reinforcing agents" and "network builders." Their three-dimensional structure helps to form a dense physical cross-linked network on the fiber surface, which helps to improve the toughness, abrasion resistance, and integrity of the interfacial layer, directly contributing to low fuzz and high processing smoothness. At the same time, the high density of epoxy groups on their surface can pre-react with other components and form a deeper interpenetrating network structure with the resin matrix, thereby improving the interfacial mechanical properties to a higher level.
[0029] As an example, the diamino silane coupling agent of this application can be selected as A-1120 or KH-792; the vinyl silane coupling agent containing alkenyl ether groups can be selected as SIVO-160 or a silane derivative having a structure similar to alkenyl ether functional groups; the epoxy-terminated hyperbranched polysiloxane can be selected as a hyperbranched polysiloxane with an epoxy value of 0.15~0.25 mol / 100g and a viscosity of 2000~8000mPa·s.
[0030] In one embodiment of this application, the effective components, based on the percentage of the solid mass of each effective component to the solid mass of the wetting agent, include: 7-26% silane coupling agent, 35-70% film-forming agent, 7-22% lubricant, 2-7% crosslinking agent, 1.5-6.5% compatibilizer, and 1.5-6% pH adjuster; preferably, the effective components include: 10-22% silane coupling agent, 46-63% film-forming agent, 9-18% lubricant, 3-6% crosslinking agent, 2-4.5% compatibilizer, and 2-4% pH adjuster.
[0031] This application optimizes the formulation of the sizing agent to fully leverage the synergistic effects between its components. Specifically, maintaining the solid mass of the coupling agent within the aforementioned range helps balance interfacial strength and system stability. Maintaining the solid mass of the film-forming agent within the aforementioned range ensures good processing suitability and emulsion stability, resulting in optimal overall performance of the final glass fiber product in terms of wetting speed, hair control, process smoothness, and the static mechanical properties of the composite material. Controlling the proportion of lubricant within the aforementioned range reduces the risk of insufficient lubricant coverage leading to reduced lubrication and increased hair and processing resistance, while also mitigating the risk of excessive plasticization of the interfacial layer, weakened fiber bundle strength, and interference with the interfacial interactions of other components due to excessively high lubricant content. By limiting the formulation and content range, the sizing agent can fully utilize its synergistic lubrication and bundle-forming functions, achieving extremely low hair and ultra-high smoothness without affecting the overall reactivity and final interfacial strength of the system. The dosage of the crosslinking agent needs to balance reactivity and system stability. Controlling the solid mass of the crosslinking agent within the aforementioned range is beneficial for the formation of a strong interfacial crosslinking structure without affecting the processability of the sizing agent. Furthermore, setting the proportion of the solid mass of the compatibilizer within the aforementioned range helps it fully exert its interfacial building function and reduces the risk of inappropriate compatibilizer dosage interfering with system stability and process performance. Further optimization of each component within this range is more conducive to the formation of a sufficient and effective active interfacial layer on the fiber surface, thus helping to ensure excellent static and dynamic mechanical properties of the composite material. Simultaneously, controlling the theoretical solid component of the pH adjuster within the aforementioned range helps ensure the hydrolytic activity of the coupling agent and the pH stability of the system, while reducing the risk of excessive acidic components adversely affecting the performance of other components or the fiber surface. Further optimized proportions result in the sizing agent possessing superior processability and mechanical properties.
[0032] In one embodiment of this application, the lubricant is a mixture of fatty acid esters and modified silicone oils, preferably a mixture of oligomeric fatty acid ester derivatives and reactive polyether modified silicone oils; and / or, the pH adjuster is citric acid and / or glacial acetic acid.
[0033] As a key functional component in glass fiber impregnation, the lubricant's core role is to balance the bundle protection and processing lubrication of the glass fibers, thereby contributing to the smoothness of the entire process from fiber drawing to composite material molding. The lubricant selected in this application is a compound system of oligomeric fatty acid ester derivatives and reactive polyether-modified silicone oil. Specifically, the oligomeric fatty acid ester derivatives, due to their molecular weight and flexible chain structure, can effectively penetrate between the fiber monofilaments, providing uniform internal lubrication and sufficient soft bundle formation. This helps reduce the risk of monofilament unraveling and fuzzing, and also reduces the risk of the impregnating agent forming a dense barrier that hinders resin penetration, thus facilitating ultra-high-speed impregnation. The reactive polyether-modified silicone oil forms a highly effective slip-resistant protective film on the outer surface of the fiber bundle. Its polyether segments endow the impregnating agent with excellent resin affinity and low-friction properties, while the hydrolyzable reactive groups it contains help anchor it to the fiber surface, providing a durable and stable external lubrication effect, thereby ensuring the smoothness of the pultrusion process and reducing wear.
[0034] The pH adjuster selected in this application is citric acid and / or glacial acetic acid. Its main function is to provide a hydrolytic environment for different coupling agents and adjust the pH value of the wetting agent system to a stable weakly acidic range, thereby helping to inhibit other reactions and precipitation phenomena between the components and ensuring that the wetting agent as a whole has good storage stability and process applicability.
[0035] In one embodiment of this application, the crosslinking agent is a carbodiimide crosslinking agent; and / or, the compatibilizer is a phenylboronic acid graft copolymer.
[0036] Although the crosslinking agent is used in a low amount in the impregnating agent, it plays an important role in improving the interfacial strength and durability of the composite material. The carbodiimide crosslinking agent selected in this application has good stability in the aqueous system. During the drying and pultrusion processes, it can undergo a highly efficient crosslinking reaction with the carboxyl and hydroxyl groups in the film-forming agent and the amino groups in the coupling agent to generate stable acylurea or isourea structures, thereby forming a high-density crosslinked network in the resin-fiber interface region, which helps to enhance interlayer bonding, fatigue resistance and mechanical strength.
[0037] Compatibilizers, as key components for achieving high-performance interfaces between fibers and resins, primarily improve the compatibility and bonding strength between the surface of inorganic glass fibers and various organic resin matrices. The phenylboronic acid graft copolymer selected in this application belongs to a class of intelligent interface modifiers with dynamic response characteristics. In the alkaline environment of the wetting agent, the phenylboronic acid groups of this copolymer can form strong dynamic covalent bonds with the cis-diol structures on the copolymer chain, thus firmly anchoring it to the fiber surface. When it enters an acidic or neutral resin curing system, these dynamic covalent bonds reversibly break, releasing the polymer's molecular mobility, allowing its resin-loving segments to fully extend and deeply diffuse into the resin matrix, forming a strong and tough physical interpenetrating network. This helps the copolymer dynamically optimize the interface structure for resins with different polarities and reactivity (such as EP, UP, VE, PU), simultaneously achieving broad-spectrum resin compatibility and ultra-high-speed wetting capabilities.
[0038] In another typical embodiment of this application, a method for preparing the above-mentioned sizing agent for direct glass fiber yarn is provided, comprising: step S1: mixing raw materials including water, pH adjuster and silane coupling agent to obtain a first mixed solution; step S2: mixing film-forming agent and lubricant with the first mixed solution to obtain a second mixed solution; step S3: adding water to the second mixed solution to obtain a third mixed solution, wherein the mass percentage of water in the third mixed solution is ≥75%; step S4: mixing crosslinking agent and compatibilizer with the third mixed solution to obtain a fourth mixed solution; and step S5: adding the remaining water to the fourth mixed solution to obtain the sizing agent.
[0039] This application optimizes the design of each component and its ratio to produce a sizing agent that coats glass fibers with broad-spectrum resin compatibility, ultra-high-speed wetting capability, extremely low fuzz, excellent process smoothness, and superior interfacial bonding performance. This sizing agent is suitable for various resin systems such as epoxy and polyester, and can be used in various molding processes such as winding, pultrusion, and weaving. It is particularly suitable for single-strand pultruded composite materials where interfacial performance and process efficiency are extremely important, resulting in outstanding mechanical properties of the finished products. Furthermore, this application employs a step-by-step feeding process to improve the stability and uniformity of the sizing agent. Specifically, firstly, the silane coupling agent and pH adjuster are premixed to ensure complete hydrolysis of the silane coupling agent, preventing precipitation from subsequent reactions with other components. Secondly, the film-forming agent and lubricant are diluted separately before addition to prevent uneven dispersion or demulsification caused by direct mixing of high-viscosity components. Finally, a crosslinking agent and compatibilizer are introduced in an environment with sufficient water (≥75%), utilizing the dilution effect to inhibit premature crosslinking of the crosslinking agent, ensuring the uniformity and stability of the entire system. By using the step-by-step feeding method described above, the compatibility problem between multiple components is solved, and the storage stability and coating performance consistency of the product are improved.
[0040] To further optimize the preparation process of the above-mentioned sizing agent, in one embodiment of this application, the preparation method of the above-mentioned sizing agent for direct glass fiber yarn specifically includes: Step S1: Add 25%~40% of the total mass of the sizing agent to a container with deionized water, then add a pH adjuster and 20~30 times the amount of deionized water and stir thoroughly, then add a hydrolyzed silane coupling agent to ensure the solution is clear; Step S2: Dilute the film-forming agent with a small amount of deionized water and add it to the container, wherein the mass of the deionized water is 3~5 times the mass of the film-forming agent; add lubricant... Step S3: Dilute the lubricant with deionized water and add it to the container, wherein the mass of the deionized water is 2 to 4 times the mass of the lubricant; Step S4: Add sufficient amount of deionized water to ensure that the total water volume is ≥75%, and stir evenly; Step S5: Dilute the crosslinking agent with deionized water and add it to the container, wherein the mass of the deionized water is 3 to 5 times the mass of the crosslinking agent; Dilute the compatibilizer with deionized water and add it to the container, wherein the mass of the deionized water is 5 to 8 times the mass of the compatibilizer; Step S6: Add the remaining deionized water to the container, stir evenly, and the product is obtained.
[0041] The more specific preparation process and condition control described above further improve the process stability, making the final sizing agent system more uniformly dispersed and with better storage stability. This further reduces the risk of other reactions, precipitation, or premature cross-linking between components, thereby helping to improve the bundle properties, low fuzz characteristics, and interfacial bonding strength of the composite material.
[0042] In one embodiment of this application, the preparation steps of the phenylboronic acid graft copolymer compatibilizer include: dissolving polyvinyl alcohol in an alkaline aqueous solution with a pH of 8.0 to 10.0, adding an activated carboxyphenylboronic acid derivative, and stirring the reaction at a temperature of 40 to 80°C for 4 to 12 hours; after the reaction is completed, adjusting the pH to acidic to precipitate the product, and then washing and drying to obtain the phenylboronic acid grafted polyvinyl alcohol copolymer.
[0043] The above preparation process facilitates the stable anchoring of the compatibilizer on the fiber surface in the alkaline wetting agent, and its release and full diffusion during the curing process of the acidic resin, thereby forming a dynamic interpenetrating network at the fiber-resin interface.
[0044] In another typical embodiment of this application, a glass fiber is provided, which is produced by coating with an impregnating agent, characterized in that the impregnating agent is the above-mentioned glass fiber direct yarn impregnating agent, or the impregnating agent is prepared by the above-mentioned preparation method.
[0045] This application optimizes the design of each component and its ratio of the sizing agent, so that the glass fiber coated with the prepared sizing agent has broad-spectrum resin compatibility, ultra-high speed wetting ability, extremely low fuzz, excellent process smoothness and interfacial properties; it can be widely used in various resin systems such as epoxy and polyester, and is suitable for various molding processes such as winding, pultrusion and weaving, especially suitable for the demanding single-strand pultrusion process, with excellent mechanical properties.
[0046] In another typical embodiment of this application, the application of the glass fiber direct yarn impregnating agent as described above in the preparation of glass fiber composite yarn is provided.
[0047] Applying the sizing agent of this application to the preparation of yarns for glass fiber composite materials helps improve the rapid wetting of glass fibers in various resins such as epoxy resin and unsaturated polyester resin, as well as the interfacial bonding strength. It solves the problems of fuzz and loose fibers in high-speed pultrusion processes, helping to ensure smooth production and reduce wear. The resulting composite material exhibits excellent mechanical properties, making it particularly suitable for applications requiring stringent performance characteristics in single-strand pultruded composite materials.
[0048] Example 1
[0049] A method for preparing a glass fiber impregnating agent includes the following steps:
[0050] Step S1: Add 30% of the total mass of the wetting agent to the container with deionized water, then add the pH adjuster and 25 times the amount of deionized water and stir thoroughly. Then add the hydrolyzed silane coupling agent to ensure the solution is clear.
[0051] Step S2: Dilute the film-forming agent with a small amount of deionized water and add it to the container, wherein the mass of the deionized water is 4 times the mass of the film-forming agent;
[0052] Dilute the lubricant with deionized water and add it to the container, wherein the mass of the deionized water is 3 times the mass of the lubricant;
[0053] Step S3: Add enough deionized water to ensure the total water volume is ≥75%, and stir well;
[0054] Step S4: Dilute the crosslinking agent with deionized water and add it to the container, wherein the mass of the deionized water is 4 times the mass of the crosslinking agent;
[0055] The compatibilizer is diluted with deionized water and then added to the container, wherein the mass of the deionized water is 6 times the mass of the compatibilizer.
[0056] Step S5: Add the remaining deionized water to the container, stir well, and the product is obtained.
[0057] The preparation steps of the phenylboronic acid graft copolymer compatibilizer include: dissolving polyvinyl alcohol in an alkaline aqueous solution with a pH of 9.0, adding an activated carboxyphenylboronic acid derivative, and stirring the reaction at 70°C for 12 hours; after the reaction is completed, adjusting the pH to acidic to precipitate the product, and then washing and drying to obtain the phenylboronic acid grafted polyvinyl alcohol copolymer.
[0058] The specific components of the glass fiber impregnating agent are shown in Table 1, and the effective components include:
[0059] Aminosilane coupling agent (A-1120 (Momentive));
[0060] Vinylsilane coupling agent (Dynasylan 6598 (Evonik));
[0061] Epoxy silane coupling agent (EP0409 (HybridPlastics));
[0062] First film-forming agent (EPIKOT6520-WH-53 (Huntsman));
[0063] Second film-forming agent (Neoxil962 (INEOS));
[0064] Lubricant 1 (Loxanol MI6840 (BASF));
[0065] Lubricant 2 (KF-6011 (Shin-Etsu));
[0066] Crosslinking agent (Carbodilite V-02 (Nisshinbo));
[0067] Compatibilizer (phenylboronic acid graft copolymer, homemade);
[0068] pH adjuster (citric acid).
[0069] The specific preparation process of the glass fiber impregnating agent in Examples 2 to 10 is the same as that in Example 1, and the specific components and contents are shown in Tables 1 and 2.
[0070] In Examples 1 to 3, the solid content was 5.0 wt%, the molecular weight of the first film-forming agent was 800, and the molecular weight of the second film-forming agent was 600; in Examples 4 to 7, the solid content was 7.0 wt%, the molecular weight of the first film-forming agent was 1200, and the molecular weight of the second film-forming agent was 900; in Examples 8 to 10, the solid content was 9.0 wt%, the molecular weight of the first film-forming agent was 1500, and the molecular weight of the second film-forming agent was 1200. The values in Tables 1 and 2 represent the percentage of the solid mass of each effective component to the total solid mass of the wetting agent.
[0071] Example 11
[0072] The difference from Example 1 lies in the percentage of the solid mass of each effective component relative to the total solid mass of the wetting agent:
[0073] Aminosilane coupling agent (A-1120 (Momentive)) 12.5%;
[0074] Vinyl silane coupling agent (Dynasylan 6598 (Evonik)) 4.5%;
[0075] Epoxy silane coupling agent (EP0409 (HybridPlastics)) 3.0%;
[0076] First film-forming agent (EPIKOT6520-WH-53 (Huntsman)) 46.0%;
[0077] The second film-forming agent (Neoxil962 (INEOS)) was 11.5%;
[0078] Lubricant 1 (Hydrolube® 723 (Michelman)) 3.0%;
[0079] Lubricant 2 (KF-6011 (Shin-Etsu)) 9.0%;
[0080] Crosslinking agent (Carbodilite V-02 (Nisshinbo)) 4.0%;
[0081] Compatibilizer (phenylboronic acid graft copolymer, self-made) 3.5%;
[0082] pH adjuster (citric acid) 3.0%;
[0083] The solid content of the wetting agent is 7.0 wt%.
[0084] Example 12
[0085] The difference from Example 11 is the percentage of the solid mass of each effective component to the total solid mass of the wetting agent:
[0086] Aminosilane coupling agent (A-1120 (Momentive)) 12.0%;
[0087] Vinyl silane coupling agent (Dynasylan 6598 (Evonik)) 5.0%;
[0088] Epoxy silane coupling agent (EP0409 (HybridPlastics)) 3.0%;
[0089] First film-forming agent (EPIKOT3522-W-60A (Hexion)) 46.0%;
[0090] Second film-forming agent (Norpol 20-70W (Reichhold)) 10.0%;
[0091] Lubricant 1 (Emulsogen TS200 (Clariant)) 5.0%;
[0092] Lubricant 2 (KF-6011 (Shin-Etsu)) 8.0%;
[0093] Crosslinking agent (CarbodiliteSV-02 (Nisshinbo)) 5.0%;
[0094] Compatibilizer (phenylboronic acid graft copolymer, self-made) 3.0%;
[0095] pH adjuster (citric acid) 3.0%;
[0096] Example 13
[0097] The difference from Example 11 is that the percentage of silane coupling agent in the total mass of the wetting agent is 30%, and the mass ratio of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent is 13%:12%:5%.
[0098] Example 14
[0099] The difference from Example 11 is that the percentage of silane coupling agent in the total mass of the wetting agent is 30%, and the mass ratio of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent is 25%:3%:2%.
[0100] Example 15
[0101] The difference from Example 11 is that the ratio of film-forming agents is changed, with the ratio of first film-forming agent to second film-forming agent being 1:1.
[0102] Example 16
[0103] The difference from Example 11 is that the lubricant is a nonionic paraffin emulsion and an oligomeric fatty acid ester derivative.
[0104] The effective components, defined as the percentage of the solid mass of each effective component relative to the solid mass of the wetting agent, include:
[0105] Aminosilane coupling agent (KH-550) 12.5%;
[0106] Vinylsilane coupling agent (A-174) 4.5%;
[0107] Epoxy silane coupling agent (A-187) 3.0%;
[0108] First film-forming agent (EPOKOTE862 (HEXION)) 46.0%;
[0109] Second film-forming agent (Setal® 91001 (Allnex)) 11.5%;
[0110] Lubricant 1 (Loxanol MI6840 (BASF)) 3.0%;
[0111] Lubricant 2 (Armostat® 4000 (AkzoNobel)) 9.0%;
[0112] Crosslinking agent (BayhydurBLXP2706 (Covestro)) 4.0%;
[0113] Compatibilizer (Zemac® E60P (Vertellus)) 3.5%;
[0114] pH adjuster (citric acid) 3.0%;
[0115] As shown in Tables 1 and 2, the values in Table 1 are the percentage of the solid mass of each effective component in Examples 1-5 to the total solid mass of the wetting agent, the values in Table 2 are the percentage of the solid mass of each effective component in Examples 6-11 to the total solid mass of the wetting agent, and the values in Table 3 are the percentage of the solid mass of each effective component in Examples 12-16 to the total solid mass of the wetting agent.
[0116] Table 1
[0117]
[0118] Table 2
[0119]
[0120] Table 3
[0121]
[0122] Comparative Example 1
[0123] The difference from Example 1 is that, based on the percentage of the solid mass of each effective component to the solid mass of the wetting agent, the effective components include:
[0124] Vinylsilane coupling agent (A-174) 25.0%;
[0125] Epoxy silane coupling agent (KH-560) 5.0%;
[0126] First film-forming agent (EPIKOT828 (HEXION)) 40.0%;
[0127] The second film-forming agent (Norpol 430 (Reichhold)) was 9.0%;
[0128] Lubricant (Pluriol E1000 (BASF)) 15.0%;
[0129] pH adjuster (glacial acetic acid) 6.0%;
[0130] The preparation method includes the following steps:
[0131] (1) Add 30% of the total amount of water to a container equipped with a variable speed stirrer, and add the pH adjuster and silane coupling agent in sequence, stirring until the solution is clear;
[0132] (2) Dilute the film-forming agent with 4 times its weight of water and add it to the container;
[0133] (3) Dilute the lubricant with 5 times its weight of water and add it to the container;
[0134] (4) Finally, add the remaining water to the container, stir well, and the finished product is obtained.
[0135] Comparative Example 2
[0136] The difference from Example 1 is that, based on the percentage of the solid mass of each effective component to the solid mass of the wetting agent, the effective components include:
[0137] Aminosilane coupling agent (A-1100) 22.0%;
[0138] Vinylsilane coupling agent (KH-570) 5.0%;
[0139] First film-forming agent (Araldite GY250 (Huntsman)) 38.0%;
[0140] Second film-forming agent (Neoxil 862 (INEOS)) 15.0%;
[0141] Lubricant (Sokalan D50 (BASF)) 8.0%;
[0142] Crosslinking agent (BayhydurBLXP2706) 5.5%;
[0143] pH adjuster (glacial acetic acid) 6.5%;
[0144] The preparation method includes the following steps:
[0145] (1) Add water equal to 30% of the total mass of the wetting agent to a container equipped with a variable speed stirrer, and then slowly add the pH adjuster and silane coupling agent in sequence, stirring until the solution is clear;
[0146] (2) Dilute the film-forming agent with a small amount of water and add it to the container, wherein the mass of water is 4 times the mass of the film-forming agent;
[0147] (3) Dilute the lubricant with water and add it to the container, wherein the mass of water is 5 times the mass of the lubricant;
[0148] (4) Dilute the crosslinking agent with water and add it to the container, wherein the mass of water is 6 times the mass of the crosslinking agent;
[0149] (5) Finally, add the remaining water to the container and stir well to obtain the product.
[0150] Performance testing
[0151] Combustible content (wt%): determined according to GB / T9914.2-2013 "Glass fiber test methods - Part 2: Moisture content, density and non-volatile content". Instrumentation: an analytical balance with an accuracy of 0.1 mg and a muffle furnace with a temperature control accuracy of ±1℃ were used. Crucible preparation: Take a clean porcelain crucible, ignite it at 600℃ to constant weight, cool it to room temperature in a desiccator, weigh it, and record the mass m0; Sample weighing: Weigh about 1-2g of glass fiber sample, put it into the above crucible, accurately weigh the total mass, and record it as m1; Ignition treatment: Place the crucible containing the sample into a muffle furnace, heat it to 600±10℃, and ignite it for 1 hour to completely decompose and volatilize the organic impregnating agent; Cooling and weighing: After ignition, take out the crucible, cool it to room temperature in a desiccator, weigh it, and record its mass as m2. Calculate the combustible content: C=100%×(m1-m2) / (m1-m0); Perform 3 parallel tests for each sample, take the arithmetic mean as the final result, and retain the result to two decimal places.
[0152] Tensile strength (N / tex): Determined according to national standard GB / T7690.3-2013 "Test Methods for Glass Fibers - Part 3: Determination of Tensile Strength and Deformation of Monofilaments". Testing equipment includes: Monofilament tensile tester: The accuracy level should meet the requirements of GB / T7690.3-2013, with an indication error not exceeding ±1% and a minimum reading not exceeding 0.1 cN. Clamps: Special clamps suitable for glass fiber monofilaments, ensuring moderate clamping force to prevent slippage at the clamping point and avoid stress concentration leading to sample breakage near the clamping point. Gauge gauge: Used to set the test gauge length; in this embodiment, the test gauge length is 50 mm. Cutting blade: Used to cut the monofilament. Testing environment: Standard test atmospheric conditions, temperature (20±5)℃, relative humidity (65±5)%. The sample needs to be conditioned in standard atmosphere for at least 24 hours. Specific testing steps include: Sample preparation: Randomly select an appropriate amount of yarn from the glass fiber yarn to be tested. Using a monofilament separator or tweezers, carefully separate individual glass fiber monofilaments from the yarn bundle. Avoid stretching, bending, or abrasive damage to the monofilaments during the process. Discard any monofilaments with obvious surface defects, nodules, or damage. Install the sample: Secure both ends of the monofilament to the upper and lower clamps of the tensile testing instrument. Adjust the monofilament to maintain its natural straightness, aligning its axis with the center line of the clamps, avoiding lateral forces or initial bending. Adjust the gauge length to ensure an effective test gauge length of 50 mm between the two clamps. Parameter settings: Set the tensile speed. According to GB / T7690.3-2013 and the characteristics of glass fiber, the tensile speed used in this embodiment is 10 mm / min. Start the tensile testing instrument; the monofilament is stretched at the set constant speed. Record the maximum load (unit: cN or N) at which the monofilament breaks. At least 100 valid monofilaments should be tested for each sample group. If a monofilament breaks at the clamp or the fracture point is outside the gauge length, the data is invalid and resampling and testing are required until a sufficient number of valid data are obtained. Calculate the arithmetic mean of all valid test data, and determine the linear density of the glass fiber direct yarn. The monofilament breaking strength is the ratio of the average monofilament breaking load to the average monofilament linear density, which is taken as the final test result.
[0153] High-tension hairiness (mg / kg): Under a set tension (100 mN), the yarn is passed through a special hairiness collection friction roller at a uniform speed. The hairiness that is rubbed off is adsorbed and collected by filter paper. The mass difference of the filter paper before and after adsorption is weighed and converted into the hairiness mass produced per unit mass of glass fiber. The result is expressed in milligrams per kilogram (mg / kg).
[0154] Winding smoothness (number of unwinding / 10 rolls): 10 rolls of finished yarn are continuously winded, and the unwinding process of the bobbins is monitored throughout. The total number of times that problems such as internal yarn bundle slippage, unwinding, and tangled yarn occur is counted as the final result. The lower the number, the better the winding smoothness.
[0155] Impregnation status of epoxy yarn unidirectional board composite products: After the yarn is wound into a board in the 0° direction, the composite material is formed by vacuum infusion of resin. The impregnation time and impregnation status are recorded throughout the process to evaluate the impregnation performance of the yarn.
[0156] Impregnation status of unidirectional polyester yarn composite products: After the yarn is wound into a board at 0°, polyester is vacuum-infused to form a composite material. The impregnation time and impregnation status are recorded throughout the process to evaluate the impregnation performance of the yarn.
[0157] Epoxy ASTM-D2343 Tensile Strength (MPa): Based on the principles of ASTM D 3039 / GB / T20310, the tensile strength of glass fiber / epoxy composites is tested. Specimen Preparation: The glass fiber yarn to be tested is impregnated with epoxy resin using a vacuum infusion process. After curing, it is cut into standard-sized specimens (25 mm wide, 2 mm thick). Specimen Conditioning: Condition in a standard atmospheric environment (temperature 23±2℃, relative humidity 50±5%RH) for at least 40 hours. Testing Procedure: The test is performed using a universal testing machine. The specimen is subjected to uniaxial tension at a tensile speed of 5 mm / min, and the maximum load value is recorded. Tensile Strength (MPa) = Maximum Load (N) / Specimen Cross-sectional Area (mm²) 2 The average value of the test results of 5 parallel specimens is taken as the final tensile strength value.
[0158] Polyester ASTM-D2344 Tensile Strength (MPa): Tensile strength of glass fiber / polyester composites is tested according to ASTM D2344 and GB / T20310-2006. Specimen Preparation: The glass fiber yarn to be tested is impregnated with unsaturated polyester resin using a dry film pressing or vacuum infusion process. After curing, it is cut into standard-sized specimens (25 mm wide, 2 mm thick). Specimen Conditioning: Condition in a standard atmospheric environment (temperature 23±2℃, relative humidity 50±5%RH) for at least 40 hours. Testing Procedure: The test is performed using a universal testing machine. The specimen is subjected to uniaxial tension at a tensile speed of 5 mm / min, and the maximum load value is recorded. Tensile Strength (MPa) = Maximum Load (N) / Specimen Cross-sectional Area (mm²) 2 The average value of the test results of 5 parallel specimens is taken as the final tensile strength value.
[0159] The above performance tests were conducted on the glass fiber direct yarn produced by the above experimental examples and comparative examples using the impregnating agent. The test results are listed in Tables 4 and 5.
[0160] Table 4
[0161]
[0162] Table 5
[0163]
[0164] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:
[0165] Silane coupling agents are key components in glass fiber impregnation systems, their core function being to construct a stable interfacial bridge between the inorganic glass surface and the organic polymer material. This function relies on their unique amphiphilic molecular structure. Film-forming agents constitute the main solid component in glass fiber impregnation formulations, and their performance has a decisive impact on the key processes and final performance of the fibers. Specifically, on the one hand, film-forming agents not only help enhance the cohesion between monofilaments and improve the abrasion resistance of the protective film, thus contributing to excellent fiber forming and bundling; on the other hand, they help improve the yarn's permeability under high-speed processing conditions, reducing defects such as fuzz and loose fibers. Simultaneously, the characteristics of film-forming agents have a significant impact on the interfacial bonding quality between the fiber and the resin matrix, and are one of the key factors in obtaining excellent interfacial bond strength and macroscopic mechanical properties of composite materials. By using silane coupling agents in combination with film-forming agents, fiber bundle cohesion and abrasion resistance are ensured while effectively avoiding interfacial embrittlement caused by excessive silane coupling agents and increased fuzzing due to insufficient film-forming agents. This compound system of silane coupling agents and film-forming agents can reduce fiber surface energy, facilitating rapid resin penetration and thus meeting the production requirements of high-linear-speed pultrusion processes. Furthermore, controlling the solid content of the sizing agent within the aforementioned range helps promote good flowability and coating uniformity during high-speed fiber drawing, reducing the risks of high viscosity and thick film due to high solid content, and high drying energy consumption and uneven distribution due to low solid content. It also further promotes the complete hydrolysis of the silane coupling agent and the stable formation of the interfacial cross-linking network. Therefore, by controlling the content of each component within the above range, their synergistic effect can be more fully realized, so that the glass fiber coated with the sizing agent of this application has broad-spectrum resin compatibility, ultra-high speed wetting ability, extremely low fuzz, excellent process smoothness and interfacial properties; it can be widely used in various resin systems such as epoxy and polyester, and is suitable for various molding processes such as winding, pultrusion and weaving, especially suitable for the field of single-strand pultrusion composite materials with strict requirements, and the prepared composite material has excellent mechanical properties.
[0166] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A sizing agent for glass fiber direct yarn, said sizing agent comprising an effective component and water, characterized in that, The solid content of the wetting agent is 5wt%~9wt%; the effective components include, based on the percentage of the solid mass of each effective component to the total solid mass of the wetting agent: 5-30% silane coupling agent; 32-75% film-forming agent; 5-25% lubricant; 1-9% crosslinking agent; 1-8% compatibilizer; 1-7% pH adjuster; The film-forming agent includes a first film-forming agent and a second film-forming agent. The first film-forming agent is selected from any one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin and phenolic type epoxy resin. The second film-forming agent is selected from any one or more of isophthalic unsaturated polyester, orthophthalic unsaturated polyester and dicyclopentadiene unsaturated polyester.
2. The sizing agent for glass fiber direct yarn according to claim 1, wherein the mass ratio of the first film-forming agent to the second film-forming agent is 2:1 to 6:1; and / or, the first film-forming agent is a hydrogenated bisphenol A type epoxy resin emulsion; the second film-forming agent is an aqueous isophthalic unsaturated polyester emulsion; and / or, the molecular weight of the first film-forming agent is 800 to 1500; the molecular weight of the second film-forming agent is 600 to 1200.
3. The impregnating agent for glass fiber direct yarn according to claim 1, characterized in that, The silane coupling agent is a mixture of aminosilane coupling agent, vinylsilane coupling agent and epoxysilane coupling agent, and the mass ratio of the aminosilane coupling agent, the vinylsilane coupling agent and the epoxysilane coupling agent is 8~20%:3~12%:2~5%.
4. The impregnating agent for glass fiber direct yarn according to claim 3, characterized in that, The aminosilane coupling agent is a diamino silane; the vinylsilane coupling agent is a vinyl silane containing an alkenyl ether group; and the epoxysilane coupling agent is an epoxy-terminated hyperbranched polysiloxane.
5. The impregnating agent for glass fiber direct yarn according to any one of claims 1 to 4, characterized in that, The effective components, defined as the percentage of the solid mass of each of the effective components relative to the solid mass of the wetting agent, include: 7-26% of the silane coupling agent; 35-70% of the film-forming agent; 7-22% of the aforementioned lubricant; 2-7% of the crosslinking agent; 1.5-6.5% of the compatibilizer; 1.5-6% of the pH adjuster; Preferably, the effective component comprises: 10-22% of the silane coupling agent; 46-63% of the film-forming agent; 9-18% of the lubricant; 3-6% of the crosslinking agent; 2-4.5% of the compatibilizer; 2-4% of the pH adjuster.
6. The impregnating agent for glass fiber direct yarn according to any one of claims 1 to 5, characterized in that, The lubricant is a mixture of fatty acid esters and modified silicone oils, preferably a mixture of oligomeric fatty acid ester derivatives and reactive polyether modified silicone oils; and / or the pH adjuster is citric acid and / or glacial acetic acid.
7. The impregnating agent for glass fiber direct yarn according to any one of claims 1 to 6, characterized in that, The crosslinking agent is a carbodiimide crosslinking agent; and / or, the compatibilizer is a phenylboronic acid graft copolymer.
8. A method for preparing an impregnating agent for glass fiber direct yarn according to any one of claims 1 to 7, characterized in that, The preparation method includes: Step S1: Mix the raw materials including water, pH adjuster and silane coupling agent to obtain the first mixed solution; Step S2: Mix the film-forming agent and lubricant with the first mixed solution to obtain a second mixed solution; Step S3: Add water to the second mixed solution to obtain a third mixed solution, wherein the mass percentage of water in the third mixed solution is ≥75%; Step S4: Mix the crosslinking agent and compatibilizer with the third mixed solution to obtain the fourth mixed solution; Step S5: Add the remaining water to the fourth mixed solution to obtain the wetting agent.
9. A type of glass fiber, produced by coating with a sizing agent, characterized in that, The sizing agent is the glass fiber direct yarn sizing agent according to any one of claims 1 to 7, or the sizing agent is prepared by the preparation method according to claim 8.
10. The application of the glass fiber direct yarn impregnating agent as described in any one of claims 1 to 7 in the preparation of glass fiber composite yarn.